Development of Ecology Material Biology Modules Based Problem Solving - Yohanes Bare; Maria Novita Daplawi; Yohanes Boli Tematan (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2023)
The improvement of the learning process is carried out by innovating, one of which is the development of learning media in the field of Biology. The developed media is in the form of modules that are integrated with problem solving models on ecological materials. The purpose of this research is the Development of Problem Solving-Based Biology Learning Module on Ecological Materials. This research model is a research and development (Research & Development) which aims to develop a problem-solving biology-based learning module on ecological materials. Research and development R&D is the process used to develop and validate products. This research procedure uses the development model developed by Thiagarajan namely define, design, development and dissemination.